Dopaminergic microtransplants into the substantia nigra of neonatal rats with bilateral 6-OHDA lesions. II. Transplant-induced behavioral recovery - Nikkhah, G (J Neurosci, 1995)
Transplants of fetal ventral mesencephalic (VM) dopamine neurons implanted into the substantia nigra in 6-hydroxy-dopamine (6-OHDA)- lesioned neonatal pups establish axonal connections with the denervated caudate putamen (Nikkhah et al., 1995). In the present study, we have explored the functional capabilities of these animals after they reached adulthood on a battery of spontaneous and drug-induced behavioral tasks. The results demonstrate that unilateral intranigral VM grafts in bilaterally lesioned neonates induce a marked bias in spontaneous- and stress-induced rotation contralateral to the implant not present in the lesion-only controls. Amphetamine and apomorphine induced vigorous contra- and ipsilateral rotation, respectively. Moreover, grafted animals achieved 75% of the performance level in contralateral skilled forelimb use when compared to normal controls, which was significantly above lesion-only animals (50% of normal). Spontaneous nocturnal locomotor activity was elevated 2.2-fold in the grafted animals. Sensorimotor orientation and disengage behavior was spared by the neonatal dopamine lesion and unaffected by the grafts. The level of functional restoration seen in the present study was more extensive than reported previously in neonatally 6-OHDA-lesioned rats where the VM grafts were implanted ectopically into the striatum. However, functional recovery remained incomplete also after intranigral graft placement compared to normal intact animals. The present approach should provide a new promising avenue for the continued exploration of the mechanisms involved in functional recovery and structural repair in the damaged nigrostriatal system.